Prostaglandins - universal biological regulators in the human body (literature review) - О. V. Tymoshchuk; І. S. Lembryk; Z. R. Кocherga (Zaporožskij Medicinskij Žurnal)
Recently, researchers of different industries pay great attention to the problem of prostaglandins.